Analysis of Current Tools and Methods for Optimizing The Educational Process in The Context of Digital and Technological Development - Kalmatova, Gulzat; Tagaeva, Gulmira; Segizbaeva, Nazgul; Khasanov, Navruz (International Journal of Basic and Applied Sciences, 2025)
The aim of the study was to investigate the system of optimization of the educational process based on modern digital tools and methods in the context of philological education. The study combined qualitative and quantitative methods in a mixed-methods approach. Methodological recommendations for the introduction of digital technologies in the educational process of the Faculty of Russian Philology of the Kyrgyz State University named after I. Arabaev were developed. These recommendations include mechanisms for the development of digital infrastructure, professional development programs for teachers, methods of creating and adapting educational content for philological disciplines, and tools for monitoring the effectiveness of learning. The study revealed that the use of digital tools led to a significant increase in student engagement in academic discussions by 27%, timely submission of assignments by 17%, and overall satisfaction with the learning format by 23%. A theoretical model of gradual integration of digital tools, considering the specifics of philological education, is presented. The study demonstrates the need for an integrated approach to digital transformation, considering the unique characteristics of philological disciplines, particularly the challenges of working with linguistic and literary materials in digital environments. A system of recommendations for optimizing the learning process has been developed, covering technological, organizational, methodological, and pedagogical aspects of digital transformation, with a focus on creating interactive forms of working with textual materials and developing professional competencies in the digital environment.